Influence of production systems on the properties of fresh and hardened shotcrete - Cechin, Gabriela; Stolz, Carina Mariane; Masuero, Ângela Borges (Ambiente Construído, 2018)
In modern shotcrete operations, the mixing and pumping steps are carried out using different production systems and equipment. This adds an element of uncertainty to the process because of variables such as mixer type, rotation speed, mixing time, etc. As a result, this may result in changes to the characteristics and properties of both fresh and hardened sprayed mortar and may ultimately impair the performance of the rendering material. This study assesses the influence of production systems, particularly the mixing process, on the properties of fresh and hardened sprayed mortar. The methods used comprehend the collection and testing of mortar samples produced in wet-mix and dry-mix shotcrete systems, as well as a pre-packaged mortar batched and mixed in a laboratory mixer under controlled conditions according to the manufacturer’s instructions. Results were processed using analysis of variance (ANOVA) and multiple comparison of means using Fisher’s method. A statistically significant difference was observed in the flow table index, water retention, flexural strength and capillarity coefficient of the mortars produced using wet- and dry-mix systems.